2022
DOI: 10.1101/2022.01.26.477779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of RIGI, MDA5 and interferon alpha of duck in Duck Plague infection – a novel report

Abstract: Duck Plague (DP) or Duck viral enteritis is an acute contagious and highly fatal disease in water fowl commonly caused by Anatidalphavirus-1 belonging from Herpesviridae family and contains double stranded DNA as genetic material. Pathogen associated molecular pattern (PAMP)s when identified by Pathogen Recognition Receptor (PRR)s acts as effective immunity system action against the pathogen. Melanoma Differentiation-Associated protein 5 (MDA5) and Retionic Acid Inducible Gene I (RIG1) are protein sensor commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Each sample was run in duplicate. Analysis of real-time PCR (qRT-PCR) was performed by delta-delta-Ct (ΔΔCt) method 31,2,4,38,39,42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample was run in duplicate. Analysis of real-time PCR (qRT-PCR) was performed by delta-delta-Ct (ΔΔCt) method 31,2,4,38,39,42 .…”
Section: Methodsmentioning
confidence: 99%
“…A remarkable feature of indigenous ducks has been observed that they are even better resistant to avian influenza virus with explored molecular basis 1 . Immune response genes were identified in Bengal duck providing host resistance against duck plague 2 . Biochemical and haematological characterization has already been studied by our group 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted metabolomics uses LC‒MS, GC‒MS, NMR and other techniques to detect all small molecule metabolites (mainly endogenous small molecule compounds with a relative molecular weight less than 1000 Da) in cells, tissues, organs or organisms without bias, dynamic changes before and after stimulation or interference, screening differentially abundant metabolites through bioinformatics analysis, and conducting pathway analysis on differentially abundant metabolites to reveal the physiological mechanism of their changes [ 6 ]. At present, scholars at home and abroad have not stopped research on DEV, but they are all basic research, and the material changes in the development of the pathogenic mechanism of DEV are less involved, especially metabolome sequencing of the host's anti-viral infection response analysis [ 7 ]. At present, our laboratory has completed transcriptome sequencing of DEV-infected duck duodenum and high-throughput sequencing of the duodenum, although metabolome sequencing technology has been widely used in drug research and development or different stages of livestock and poultry as well as outside world substance changes under changing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We have explored the genomics for duck in terms of innate immune response genes 4-10 . We have explored duck immune response genes against duck plague infection 11-12 .…”
Section: Introductionmentioning
confidence: 99%